Exploring The Influence of Virtual Reality on Interpersonal Communication: A Novel Study In Communication Science - Zidnal Falah (Al-Makki Publisher, 2023)
This study aims to investigate the influence of virtual reality on interpersonal communication, focusing on aspects that have never been studied before in communication science. In an increasingly advanced digital age, virtual reality has become a phenomenon that attracts the attention of many people. However, there is still a lack of research that comprehensively reveals its impact on interpersonal communication. The research method used in this study is a combination of qualitative and quantitative approaches. Through the use of surveys and in-depth interviews, we obtain data that includes individual perceptions and experiences related to interpersonal communication in a virtual reality environment. Our respondents consisted of participants who were experienced in the use of virtual reality and those who had never used the technology before. Our results suggest that the use of virtual reality has the potential to influence various aspects of interpersonal communication, including emotional expression, nonverbal recognition, and levels of interpersonal closeness. These discoveries provide new insights into how virtual reality can enrich our communication experience in different contexts. This research makes an important contribution to the development of communication science, especially in understanding the role of new technologies such as virtual reality in shaping interpersonal interactions. The implications of this research could be used to develop practical guidelines for the use of virtual reality in interpersonal communication, as well as inform the design and development of better technologies in the future.